Psychoneuroimmunology - Ader, Robert (Elsevier/Academic Press, 2007)
Psychoneuroimmunology is the study of interactions among behavioral, neural and endocrine, and immunologic processes of adaptation. These two volumes provide a clearly written, extensively referenced summary of some of the behavioral, neural and endocrine regulators of immune responses and immunologically mediated disease processes and of the behavioral and neuroendocrine effects of immune system activity. Several chapters expand upon topics reviewed in earlier editions of this series; most chapters cover active areas of research that have not previously been reviewed. As illustrated in this fourth edition, interdisciplinary research continues to provide evidence that the brain and immune system represent a single, integrated system of defense. * Fully revised and updated fourth edition of the classic reference * Provides a neuroendocrine and immunologic perspective for the behavioral scientist * Provides a behavioral and neuroscience perspective for the immunologist * Helps the reader translate basic science findings into clinically relevant information * Provides the reader with the background for and foundation of integrative research and integrative medicine * Provides an encyclopedic resource for advanced undergraduates and for pre- and post-doctoral students as well as active researchers.